If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H + 20 = 0 Reorder the terms: 20 + H = 0 Solving 20 + H = 0 Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + H = 0 + -20 Combine like terms: 20 + -20 = 0 0 + H = 0 + -20 H = 0 + -20 Combine like terms: 0 + -20 = -20 H = -20 Simplifying H = -20
| y^2-at+7by-7ab=0 | | -1=-1/5x | | 3x-2(x+6)=-24 | | 11q-145=13 | | 4(v-4)=6v-22 | | (-7)-0= | | 0.09xX=43.43 | | 3+7=-11+2x | | -3+5(8+6)=37 | | 5bx^2-7ax=0 | | 3cosx-2=7 | | 6(m-2)+14=3(m+2)-6 | | -369+3x=12x+153 | | 2(x+7)=28-18-3(6-x) | | 0.09xX=57.51 | | x/.4-2x | | 21a-12=72 | | 2x+224=11x-10 | | 2ax-x-2ax= | | -215=5x+5(-3x-23) | | -14+x=35 | | 240/92 | | h(x)=32-8x | | 1/5r=2/2/3 | | 5x+5=-103-ux | | 1/2x=3/7/15 | | -3x-15=1/4x-2 | | 6(4x+10)= | | -2(6x-8)=-56 | | (-6+7p)=164 | | 1/6*k=-11 | | -4=4v+8 |